Arson with the Purpose of Intentional Destructing or Damaging Another's Property as a Way of Concealment of a Crime - Erdem V. Budayev (Сибирское юридическое обозрение)
The article is devoted to the uncovering and investigation of a crime, hidden in the means of arson. With the use of examples from the investigative and judicial practice of the Republic of Buryatia various methods and motives of arson committed in order to conceal other crimes are considered.